2011
DOI: 10.1097/acm.0b013e3182045a51
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Oral Health in U.S. Medical Schools: Results of a National Survey

Abstract: The majority of the responding U.S. medical schools offer very little oral health education. There are few meaningful correlations as to what contributes to schools having a more robust curriculum. Further study is needed to explore how to improve this educational void.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 5 publications
1
64
0
Order By: Relevance
“…This has been related to a lack of information regarding HNCA presented in the medical school curricula. [15,16,17] If our future healthcare providers are unaware of the association between HPV and HNCA, they cannot adequately counsel and educate their patients regarding its risks, signs, and symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been related to a lack of information regarding HNCA presented in the medical school curricula. [15,16,17] If our future healthcare providers are unaware of the association between HPV and HNCA, they cannot adequately counsel and educate their patients regarding its risks, signs, and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[14] However, it has been shown that medical students lack information regarding HNCA risk factors, oral screening guidelines, and head and neck examination techniques. [15,16,17] These studies did not examine medical student knowledge about HPV as a risk factor for head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In fact, a review of articles published in Academic Medicine from 2010 to 2012 revealed 9 national survey studies on medical schools in which the response rates were as low as 51% to 64%. [17][18][19][20][21][22][23][24][25] …”
Section: Is Response Rate a Standard For Publication?mentioning
confidence: 99%
“…The oral cavity remains a black box of unknown and often unexplored territory even to the most skilled medical practitioner. This unfortunate comfort level with the mouth being "detached" from the rest of the body may be due, in part, to the educational climate of many medical schools, where an average of 1 hour gets devoted to oral health during a 4-year medical school curriculum [3].…”
mentioning
confidence: 99%